2023
DOI: 10.3892/etm.2023.11802
|View full text |Cite
|
Sign up to set email alerts
|

FOXF1 attenuates TGF‑β1‑induced bronchial epithelial cell injury by inhibiting CDH11‑mediated Wnt/β‑catenin signaling

Abstract: Forkhead box F1 (FOXF1) has been reported to be associated with lung development. However, the role of FOXF1 in asthma is still not fully understood. In the present study, the biological role and the potential mechanism of FOXF1 was explored in transforming growth factor β1 (TGF-β1)-induced bronchial epithelial cell injury. Reverse transcription-quantitative PCR and western blotting were performed to detect the expression levels of FOXF1 and cadherin (CDH) 11 in TGF-β1-induced bronchial epithelial cells. Proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…A549 cells were used to induce the phenotypic transformation caused by TGF-β1 and Western blotting was employed to analyze the effect of Tan on the epithelial-mesenchymal transition (EMT) phenotype The results indicated that consistent with previous studies, E-cadherin levels decreased and collagen I, N-cadherin, and α-SMA expression increased after TGF-β1 treatment, but improved after treatment with Tan(Q. Chen et al, 2023 ). Therefore, the research demonstrated that Tan can suppress EMT and inhibit pulmonary fibrosis.…”
Section: Discussionsupporting
confidence: 78%
“…A549 cells were used to induce the phenotypic transformation caused by TGF-β1 and Western blotting was employed to analyze the effect of Tan on the epithelial-mesenchymal transition (EMT) phenotype The results indicated that consistent with previous studies, E-cadherin levels decreased and collagen I, N-cadherin, and α-SMA expression increased after TGF-β1 treatment, but improved after treatment with Tan(Q. Chen et al, 2023 ). Therefore, the research demonstrated that Tan can suppress EMT and inhibit pulmonary fibrosis.…”
Section: Discussionsupporting
confidence: 78%
“…Regulation of MAPK kinases upstream of p38, the human mitogen-activated protein kinase kinase (MKK), such as MKK6 and MKK1, could selectively block the production of MMPs and pro-inflammatory cytokines in FLS (Hammaker et al, 2012). In addition, ubiquitin D might be considered a possible therapeutic target for RA-FLS (Chen et al, 2023).…”
Section: Small Molecule Drugs Targeting Mapk Regulating Flsmentioning
confidence: 99%